Multidisciplinary Management of Postoperative Pancreatic Fistula - Glencer, Alexa; Kirkwood, Kim; Schwertner, Adam; Keller, Cody; Arain, Mustafa; Avila, Patrick; Hovsepian, David M. (Digestive Disease Interventions, 2021)
Postoperative pancreatic fistulas are complex, challenging problems that often take weeks, months, or longer to resolve. Multiple interventions may be required to achieve a successful outcome. As such, resolution typically involves a multidisciplinary approach by a team whose skills include abdominal imaging, specialized surgery, advanced endoscopy, and interventional radiology. Intensive resources and time are often required, which impacts both patients and their caregivers. While treatment(s) continue to improve, a primary goal of research efforts in this area is the prevention of this significant source of postoperative morbidity, mortality, and economic strain.
Keywords: postoperative complications; pancreas; pancreatic fistula; pancreatic leak